Effects of Bandura-Based Self Efficacy Training on Nurses Performance and Job Satisfaction: A Quasi-Experimental Study - Sri Suharningsih; Blacius Dedi; Kristiana Susilowati (An Idea Health Journal, 2026)
Background: High clinical workloads in referral hospital settings escalate physical and psychological demands, rendering nursing professionals vulnerable to operational stress and career burnout, which collectively undermine care quality. Self-efficacy is a pivotal internal cognitive resource for managing professional stability, clinical decision-making, and job satisfaction. This study evaluated the effects of a structured self-efficacy training program grounded in Albert Bandura’s Social Cognitive Theory on the clinical performance and job satisfaction of staff nurses. Methods: quantitative, quasi-experimental study using a nonequivalent control group pretest-posttest design was conducted at Santo Antonius Hospital, Pontianak. A sample of 68 clinical nurses was selected via stratified random sampling across 11 inpatient units and allocated into either an intervention cohort (n = 34), which completed a structured 4-session self- efficacy training program based on Bandura's four sources of efficacy, or a control cohort (n = 34), which maintained routine operational duties. Data were gathered using the validated General Self-Efficacy Scale (GSES), Nurse Performance Questionnaire, and Job Satisfaction Survey (JSS). Data were analyzed using independent-samples t-tests and Analysis of Covariance (ANCOVA) to control for baseline differences. Result: Baseline analysis confirmed demographic and psychometric homogeneity between groups before the intervention (p > 0.05). ANCOVA models revealed that the training intervention was significantly associated with post-test improvements across all dependent variables. After controlling for the covariate(s), the training had a statistically significant effect on nurses’ self-efficacy (F = 4.453, p = 0.039, ηp² = 0.064), with a medium effect size. The largest intervention effect was observed for clinical nursing performance (F = 29.462, p < 0.001, ηp² = 0.312), representing a large effect size. A statistically significant effect was also found for job satisfaction (F = 10.256, p = 0.002, ηp² = 0.136), with a medium-to-large effect size. Conclusion: Structured, Bandura-based self-efficacy training effectively enhances nurses' self-belief, clinical performance quality, and job satisfaction within demanding referral hospital environments. Hospital administrators should prioritize integrating structured psychological resilience and efficacy- building frameworks into continuous human resource development policies to foster clinical excellence and staff well-being.